New treatment methods for myocardial infarction - Sun, Bingbing; Wang, Long; Guo, Wenmin; Chen, Shixuan; Ma, Yujie; Wang, Dongwei (Frontiers in Cardiovascular Medicine, 2023)
For a long time, coronary atherosclerotic cardiovascular disease and acute myocardial infarction have been the focus and research hotspot of cardiovascular clinicians because of their high morbidity, high mortality, high disability rate and limited treatment options. Despite the continuous optimization of myocardial ischemia-reperfusion therapeutic methods and pharmacological therapies, the incidence rate of heart failure is still increasing year by year. It is speculated that the main reason for this situation is that reperfusion therapy after ischemic injury, drugs, rehabilitation and other traditional treatments are not aimed at the infarcted myocardium itself, which can't fundamentally solve the problems of myocardial pathological remodeling and the reduction of cardiac function after myocardial infarction, so it can't hold back the proceeding of heart failure after myocardial infarction. Coupled with the decline of mortality caused by acute myocardial infarction in recent years, the combination leads to an increase in the incidence of heart failure. As a new promising therapy rising at the beginning of the 21st century, cardiac regenerative medicine provides a new alternative choice and hope for the recovery of cardiac function and the prevention and treatment of heart failure after myocardial infarction. In the past two decades, regeneration engineering researchers have explored and summarized the elements such as cells, scaffolds and cytokines required for myocardial regeneration from all aspects and various levels day and night, paving the way for our later scholars to carry out relevant research, and also putting forward the current problems and directions for us. Here, we describe the advantages and challenges of Cardiac tissue engineering, a contemporary innovative therapy after myocardial infarction, in order to provide reference for clinical treatment.